A Comparative Dosimetric Evaluation of Intensity-Modulated Radiation Therapy (IMRT) and Three-Dimensional Conformal Radiotherapy (3DCRT) for Prostate Cancer with Testicular Shielding - Tali, Tavseef Ahmad; Rehman Khan, Mohsin; Ahmad Khan, Aijaz; Riaz, Adham; Javed, Saqib (Asian Pacific Journal of Cancer Care, 2024)
Background and objective: Intensity-modulated radiation therapy (IMRT) has emerged as a preferred technique for prostate cancer treatment, offering improved target coverage and organ sparing compared to three-dimensional conformal radiotherapy (3DCRT). However, the impact of testicular shielding on dosimetry in both modalities remains under investigation. Materials and Methods: This retrospective study compared dosimetric parameters of IMRT and 3DCRT for 20 patients with localized prostate cancer treated between January 2021 and January 2022. Plans for both techniques were generated, and comparisons were made regarding target volume dose uniformity, critical organ sparing, and testicular doses with the use of lead testicular shielding. Results: Significant dosimetric advantages were observed for IMRT compared to 3DCRT (p<0.005) in terms of target volume dose uniformity and critical organ sparing. However, with the implementation of lead testicular shielding, comparable testicular doses were achieved with both techniques. Conclusion: IMRT demonstrates superior dosimetric characteristics compared to 3DCRT for prostate cancer treatment. Nevertheless, when employing lead testicular shielding, both techniques achieve similar levels of testicular dose. These findings highlight the importance of appropriate shielding strategies to minimize gonadal dose while maximizing treatment efficacy for prostate cancer patients.